Personalization of Targeted Therapy in Advanced Thyroid Cancer - Fallahi, Poupak; Martina Ferrari, Silvia; Mazzi, Valeria; Vita, Roberto; Benvenga, Salvatore; Antonelli, Alessandro (Current Genomics, 2014)
Although generally the prognosis of differentiated thyroid carcinoma (DTC) is good, approximately 5% of people are likely to develop metastases which fail to respond to radioactive iodine, and other traditional therapies, exhibiting a more aggressive behavior. Nowadays, therapy is chosen and implemented on a watch-and-wait basis for most DTC patients. Which regimen is likely to work best is decided on the basis of an individual’s clinical information, but only data referring to outcomes of groups of patients are employed. To predict the best course of therapy, an individual patient’s biologic data is rarely employed in a systematic way. Anyway, the use of not expensive individual genomic analysis could lead us to a new era of patient-specific and personalized care. Recently, key targets that are now being evaluated in the clinical setting have been evidenced in the pathogenesis of these diseases. Some of the known genetic alterations playing a crucial role in the development of thyroid cancer include B-Raf gene mutations, rearranged during transfection/ papillary thyroid carcinoma gene rearrangements, and vascular endothelial growth factor receptor-2 angiogenesis pathways. The development of targeted novel compounds able to induce clinical responses and stabilization of disease has overcome the lack of effective therapies for DTC, which are resistant to radioiodine and thyroid stimulating hormone-suppressive therapy. Interestingly, the best responses have been demonstrated in patients treated with anti-angiogenic inhibitors such as vandetanib and XL184 in medullary thyroid cancer, and sorafenib in papillary and follicular DTC.
Keywords: XL184